Evaluasi dan Perbaikan Desain Pengalaman Pengguna Aplikasi Pelayanan Publik Smart Kampung Kabupaten Banyuwangi menggunakan Pendekatan Human Centered Design - Rivo Dimas Prakasa; Satrio Hadi Wijoyo; Intan Sartika Eris Maghfiroh (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Banyuwangi Regency has a smart city concept called Smart Kampung. Smart Kampung provides access to public services to the community through applications. The Smart Kampung application provides population administration services, complaints, and the latest information from Banyuwangi Regency. Based on the results of observations on the Google Play Store, problems were found that made the rating of this application only 3.1 and the results of interviews with DISKOMINFO Banyuwangi also stated that there was no evaluation that directly involved users so as to reduce user problems related to user experience, evaluation and designing solutions were needed. to these problems. This study uses the Human Centered Design (HCD) approach and the Modular Evaluation of Key Components of User Experience (Mecue) method to evaluate and improve the Smart Kampung mobile application. The results of the initial evaluation with 35 respondents produced the highest average score on the usefulness indicator with a value of 6.20 and the lowest average score on the negative emotions indicator with a value of 2.56. In addition, 3 major problems were found consisting of 14 specific problems related to interface appearance, usage flow, and information. Based on these problems, an improvement plan was carried out followed by retesting. The results of the improvement have a positive effect on all indicators on the Mecue questionnaire. The biggest increase is in the visual aesthetic indicator of 1.08 and the lowest increase is in the usefulness indicator of 0.19.